Exploring Senior High Schoolers’ Inhibiting Factors in English Writing Activities - Ni Made Kesi Sasmita; Peptia Asrining Tyas (Universitas Nurul Jadid, 2022)
This explanatory sequential mixed method study aims to determine the students’ attitudes toward the main inhibiting factor of English writing activity and skill development supported by the teacher’s perception. Beyond writing being one of the most complex languages and communication skills to be mastered, the success or failure of students in writing could also be influenced by various factors. This study discusses five factors: affective factor, writing apprehension, linguistic factor, writer’s block, and tactical factor. The eleventh-grade students and a senior English teacher of one public school in Malang became the participants in the study. This study has two types of data: qualitative and quantitative. The quantitative data are collected first, then qualitative data to support explaining or elaborate on the quantitative result. This research uses two instruments: 1) a closed-ended questionnaire to obtain quantitative data on learners’ perceptions, and 2) a semi-structured interview to draw the teacher’s perspective. The qualitative data analysis was conducted using statistical analysis and supported by statistical software, SPSS. A descriptive analysis was applied to analyze and describe the qualitative data. The main inhibiting factor in English writing activity faced by the eleventh graders of Senior High school 1 Malang was the writer’s block factor related to students’ motivational block at the beginning or during the writing process and their difficulties in developing and connecting different ideas.